The Effectiveness of Cognitive Behavioral Counseling and Cognitive Restructuring Techniques to Improve Self-Regulation in Learning and Self-Concept in Students - Novi Lolita Br Damanik; Nyoman Dantes; Luh Putu Sri Lestari; Ni Ketut Suarni (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Low student ability in managing the learning process independently and the presence of negative self-perceptions are major factors contributing to declining academic achievement and self-confidence. This study aims to examine the effectiveness of cognitive behavioral counseling using cognitive restructuring techniques in improving students’ self-regulated learning and self-concept. A quasi-experimental design with a pretest-posttest control group model was used in this study. The subjects consisted of 68 students divided into two groups: an experimental group that received the intervention and a control group that did not receive any specific treatment. The research instruments were self-regulated learning and self-concept questionnaires, both of which had been tested for validity and reliability. Data were analyzed using MANOVA to determine the differences in pretest and posttest scores on both variables. The results showed that cognitive behavioral counseling with cognitive restructuring techniques was effective in simultaneously improving students' self-regulated learning and self-concept (p < 0.05). These findings reinforce the effectiveness of cognitive restructuring techniques in the context of school counseling services, particularly in schools with lower socioeconomic backgrounds. This study also provides both theoretical and practical contributions to the development of cognitive behavioral-based counseling services in educational settings.